Effect of nutritional factors on growth and L-asparaginase production by three thermophilic coprophilous fungi - Ajmeera, Shanthi Priya; Rao, Vankudoth Koteswara; Sreelatha, B.; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Current Research in Microbiology Biotechnology, 2015)
The present study aimed to investigate the effect of nutritional factors on L-asparaginase production by three thermophilic caprophilous fungi (Thielavia terrestris, Malbranchea cinnamomea and Scytalidium thermophilum) was assessed in YES medium by substituting starch and L-asparagine so as to supply equal amount of carbon and nitrogen sources respectively. D-glucose, starch, maltose and mannitol were best source for growth and L-asparaginase production by all three thermophilic caprophilous fungi under investigation. Similarly L-asparagine, L-arginine, L-tyrosine and L-histidine were good nitrogen sources for both growth and L-asparaginase production. Production of the variance of the data showed the significant difference (P<0.05) among the three thermophilic caprophilous fungi with regards to carbon and nitrogen source.

Factors influencing L-asparaginase production by three thermophilic caprophilous fungi - Shanthipriya, A.; Rao, Vankudoth Koteswara; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (International Journal of Pharma Sciences, 2015)
Influence of medium, pH and temperature on L-asparaginase production by Thielavia terrestris, Malbranchea cinnamomea and Scytalidium thermophilum in submerged fermentation process was investigated. Maximum Lasparaginase production was recorded in the glucose medium supplemented with 0.5% L-asparagine monohydrate on 8th day of incubation. Czapek-dox medium was the next proffered medium for both biomass and L-asparaginase production by the fungi under investigation. Among different pH tried, pH 7.0 was optimum for L-asparaginase production, while enzyme production was marginal in medium with 6.0-8.0. Temperature of 45°C and 50°C were optimum for T. terrestris for growth of M. cinnamomea and S. thermophilum respectively. Maximum Lasparaginase activity of all three fungi was recorded at 45°C with varying extent was recorded. Analysis of variance of the data revealed significant differences (p-0.05) among the different culture media, pH and temperature on the production of L-asparaginase. A significant and positive correlation coefficient (R) was also observed between the growth and L-asparaginase activity of T. terrestris (0.570), M. cinnamomea (0.947) and S. thermophilum (0.948). Conclusion the culture medium and factors like pH, incubation temperature and incubation period play an important role in the L-asparaginase production by all the three thermophilic caprophilous fungi.

Influence of carbon and nitrogen source on growth, DON and NIV production by two species of fusarium isolated from finger millets - Penugonda, Shilpa; Rao, Vankudoth Koteswara; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: Influence of different carbon [C] and nitrogen [N] source on the growth and Deoxynivalenol [DON] and Nivalenol [NIV] production by Fusarium aethiopicum and Fusarium culmorum was investigated. Methods: Seven days old monosporic cultures of F. aethiopicum strain GSKUMB [KJ21085] and F. culmorum strain GSKUMB [KJ190159] were grown in CYA broth and incubated at 27±2°C on the rotary shaker at 120 rpm for 21 days. At the end of incubation period, cultures were harvested for determination of fungal growth (biomass). The resultant culture filtrates were extracted twice with ethyl acetate and concentrated. One ml of final concentrate in methanol was employed for detection of DON and NIV with the help of RP-HPLC. Results: The highest amount of DON and NIV were produced by F. aethiopicum in the presence of D-mannose and D-galactose as C source, while the highest amount of biomass was recorded on maltose and succinic acid. F. culmorum produced maximum amount of toxins in the presence of D-glucose, D-mannitol and D-fructose. Sodium nitrate was most favorable nitrogen source as it induced maximum amount of toxins by F. aethiopicum, while L-methionine, L-asparatic acid and L-tryptophan were next preferred N source. In contrast, highest biomass of fungus was obtained with L-lysine, L-glutamine and L-tyrosine. F. culmorum produced maximum amount of toxin and biomass with potassium nitrate and L-tyrosine respectively. Conclusion: Present species of Fusarium differed varied both in toxins (DON, and NIV) and biomass production. Their response of fungi under investigation towards C and N sources is also varied.

Influence of different fusarium species on seed germination and seedlings growth of finger millet (Eleusine coracana L.) - Penugonda, Shilpa; Rao, Vankudoth Koteswara; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Indian Journal of Biotechnology, 2015)
Effect of agriculturally important Fusariumspecies on the seed germination and seedling growth of finger millet (Eleusine coracana L.) was investigated. Species of Fusarium caused significant seed germination inhibition and seedling growth which varied with the species and age of the culture. Culture filtrates of F. moniliforme, F. proliferatum, F. chlamydosporum, F. aethiopicum, F. heterosporum and F. sporotrichoides were comparatively more toxic. The correlation coefficients between polished and unpolished variety of fingermillet seed germination inhibition (0.574, P=0.005), shoot elongation inhibition (0.893, P=0.0000) and root elongation inhibition (0.175, P=0.1770) with culture filtrates of different species of Fusarium was recorded. Pathogenicity studies revealed that F. roseum, F.sporotrichoides, F. proliferatum and F.oxysporum caused seedrot and seedling death. The maximumroot elongation inhibition (52.20%), mean (36.39%) andminimum(14.73%)were recorded toward the toxicity of different species of Fusarium. Significant and positive correlation (0.802, P=0.0026) between the root and shoot, (0.393, P=0.130) between shoot and leaf, (0.121, P=0.369) between root and leaf elongation inhibition of finger millet could be observed. The culture filtrates ofmajormycotoxigenic strains of Fusariumrevealed production of Zearalenone (ZEA), T2 toxin, nivalenol (NIV), Deoxynivalenol (DON) and Deoxyscripenol (DAS). Toxicity of Fusarium species to its seed germination and seedling growth may be attributed to their secondary metabolites including mycotoxins.

Inhibitory effect of essential oils on growth and ochratoxin a production by penicillium species - Rao, Vankudoth Koteswara; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Research Journal of Microbiology, 2015)
The screening of essential oil of brassica (Brassica oleracea), castor (Ricinus communis), coconut (Cocos nucifera), eucalyptus (Eucalyptus globulus), groundnut (Arachis hypogaea), neem (Azadirachta indica), palmolive (Elaeis guineensis) and sunflower (Helianthus annuus) for their efficacy against growth and OTA production by P. verrucosum and P. nordicum was performed. Neem and eucalyptus oil were most effective inhibitors of biomass and OTA production by both the species of Penicillium under investigation. P. nordicum was totally inhibited at 15 µL mLG1 concentration of neem and eucalyptus oil, while P. verrucosum was inhibited only to the extent of 77.52-92.49%. Sunflower and palmolive oils were next in their toxicity against the growth and OTA production by both the species of Penicillium under investigation. Essential oil of brassica, castor, coconut and groundnut varied in their degree of inhibition against P. verrucosum and P. nordicum. A positive correlation coefficient (R) was observed between the inhibitory effect of essential oils on growth (0.8933) and OTA production (0.9242). In conclusion, neem and eucalyptus oils proved to be potential bio-control agents and help to prevent the infestation of stored foods and feeds by 2 species of Penicillium and elaboration of OTA